Perbandingan saturasi oksigen sebelum dan sesudah menggunakan alat pelindung diri level III pada perawat di Ruang Critical Care Unit COVID-19 - Imas Yoyoh; Nita Nurmiati; Elly Purnamasari (STIKes Surya Global Yogyakarta, 2021)
The pandemic is still happening today. In treating Covid-19 patients, nurses are very susceptible to infection, so the Personal Protective Equipment (PPE) used is level III. This can cause several changes in the nurse's body such as having difficulty breathing and having an impact on decreasing oxygen saturation. The purpose of this study is to determine the difference in oxygen saturation before and after using level III personal protective equipment for nurses. This type of research was quantitative with a quasi-experimental design using a one group pre and post-test design. The population in this study were nurses in the Covid Critical Care Unit (ICU) room at Kalideres Hospital as many as 20 people.The sampling technique used was total sampling. Data were taken from a measurement of oxygen saturation with a pulse oximetry device, and it performed before and after removing level III PPE. Analysis using T-Test Dependent/Paired Sample T-Test. The results of the normality test using the Kolmogorov-Smirnov data obtained that the data was normally distributed with a p-value 0.05 The result of research showed that the average value of oxygen saturation before (pre-test) was: 97.90 while after (post-test) was: 95.20. Comparative test between oxygen saturation before and after showing results of p-value = 0,000 (p-value 0.05), so there was a significant difference between them. Conclusion: there is a significant difference between oxygen saturation before and after using level III personal protective equipment.